(untitled) - Ahmed Abd El Aal (Egyptian Journal of Petroleum)
The aim of this study is to determine the mechanical and petrophysical properties of sandstone rocks and using P-wave to correlate among these properties as well as the influence of cement which are intrinsic factors controlling the mechanical properties of clastic rocks. The field study included the description of the Lower Red Unit of the Wajid Sandstone outcrop analog section described previously, lithofacies description, identification, and rock sample collection from the subsurface section. Both X-ray diffraction, SEM and petrographic analyses indicate that the red sandstones are composed of predominantly K-feldspar and quartz grains and an illite matrix. In the laboratory work; porosity (n%), permeability (K md), apparent density g/cc, water absorption (Ab%), void index (e%), Schmidt hammer rebound hardness (SHR), uniaxial compressive strength (σc MPa)), Point load index (Pl) and ultrasonic pulse tests (Vp) were carried out. Then, the results were analyzed statistically to find the correlation coefficient between these measured parameters. The results of Vp with the mechanical and physical properties of the rocks were analyzed using the method of least squares regression. In all cases, the weakly to moderately correlation coefficient (R2) was determined for each regression. Relatively high correlation values were seen between Vp index and porosity of R2 0.60. The sandstone in the study can be classified according to the UCS classification for intact rock into very low to low strength (1–20.39 MPa) and very low velocity of sound velocity classification.